Factors that contribute to the less interest of youth in agriculture sector. Case study in rural area in Kuala Pilah, Negeri Sembilan / Nur Farahanis Anuar and Nurul Khairunnisa Mohd Yunus - Anuar, Nur Farahanis; Mohd Yunus, Nurul Khairunnisa (2022)
This study was carried out to identify the factors that contribute to the less interest of youth in agriculture sector in Kuala Pilah area. The reason we choose Kuala Pilah is because it is rural area where it close to the agriculture sector. The number of young people involved in agriculture is unfavourable. As a result, many agricultural areas in rural areas are underexplored due to a lack of interest among young people. Hence, this study is being conducted to determine the true reason why youth are uninterested in the agricultural sector. Research data will be obtained through surveys where questionnaires will be distributed to respondents virtually. In addition, some specific hypotheses are being researched where it is to determine the connection between family history and the factors that contribute to youth disinterest in agriculture. Furthermore, the purpose of this study is to look into the relationship between youth lifestyle and the factors that contribute to youth disinterest in agriculture and to evaluate the relationship between a career path and the factors that contribute to youth disinterest in agriculture.